Answer:
a) ∇f(0, 3, -2) = (-6*e⁻³, 0, 0)
b) u = -1 i + 0 j + 0 k = (-1, 0 , 0)
c) Df_u(0, 3, -2) = 6*e⁻³
d) Df_B(0, 3, -2) = (- 14/3)*(e⁻³)
Explanation:
a) We apply the formula
∇f = e∧(xyz-3)(yz) i + e∧(xyz-3)(xz) j + e∧(xyz-3)(xy) k
∇f(0, 3, -2) = e∧(-3)(-6) i + e∧(-3)(0) j + e∧(-3)(0) k = -6*e⁻³i + 0 j + 0 k
⇒ ∇f(0, 3, -2) = (-6*e⁻³, 0, 0)
b) u = ∇f / ║∇f║
we get ║∇f║ as follows
║∇f║= √((-6*e⁻³)²+(0)²+(0)²) = 6*e⁻³
⇒ u = (-6*e⁻³/6*e⁻³) i + (0/6*e⁻³) j + (0/6*e⁻³) k
⇒ u = -1 i + 0 j + 0 k = (-1, 0 , 0)
c) Df_u(P) = ∇f(0, 3, -2).u
⇒ Df_u(0, 3, -2) = (-6*e⁻³, 0, 0)(-1, 0, 0) = (-6*e⁻³)(-1)+(0)(0)+(0)(0)
⇒ Df_u(0, 3, -2) = 6*e⁻³
d) Df_B(0, 3, -2) = (-6*e⁻³, 0, 0)(7/9, 4/9, 4/9) = (-6*e⁻³)(7/9)+(0)(4/9)+(0)(4/9)
⇒ Df_B(0, 3, -2) = (- 14/3)*(e⁻³)